Kajian Psikologi Humanistik Dalam Novel Nyanyian Gurukinaya Karya Albert Purba - Oktaviani, Rizka; Puspita, Yenny; Wahidy, Achmad (ANTHOR: Education and Learning Journal, 2022)
Humanistic psychology is a theoretical approach in psychology that views the focus of problems on human behavior as a whole individual. Based on this, the problem in this research is how to study humanistic psychology in the novel Nyanyian Gurukinayan by Albert Purba. The purpose of this study is to find out, describe, and understand how the form of humanistic psychology studies in the novel Nyanyian Gurukinayan by Albert Purba. Theresearch method used is the descriptive qualitative method. Based on the results of research and discussion, it can be concluded that the novel Nyanyian Gurukinayan by Albert Purbasucceeded in fulfilling the aspects of the stratified needs according to Abraham Maslow's theory, including physiological needs, security needs, love, and belonging needs, self-esteem needs, and self-actualization needs which are depicted in the main character ancient fate.